EFEK ALOKASI DAN KONTRIBUSI SEKTOR PERTANIAN DALAM MENGHADAPI OTONOMI DAERAH DI KABUPATEN BOYOLALI - Ropingi Ropingi; Agustono Agustono (Universitas Sebelas Maret, 2006)
in OTDA era, data and information about allocation effect is very important, because its became competitive advantage in this region. THe other opportunity in investor pulled with this region. This research was done in Boyollai regency. Assessing data from BPS Central Java. Boyolali regency the data and information used in this research was data Gross Regional Domestic Product (GRDP) from 1998 to 2002. Type of data is secondary. For analysing this research used Esteban-Marquillas Shift Share Analysis (Dynamic SSA/ E-M SSA)